In situ fabrication of three-dimensional graphene films on gold substrates with controllable pore structures for high-performance electrochemical sensing - Shi, L.; Chu, Z.; Liu, Yu; Jin, W.; Xu, N. (Wiley, 2014)
In this work, novel three-dimensional graphene films (3D GFs) with controllable pore structures are directly fabricated on gold substrates through the hydrothermal reduction. An interfacial technique of the self-assembled monolayer is successfully introduced to address the binding issue between the graphene film and substrate. Adscititious silica spheres, serving as new connection centers, effectively regulate the dimensions of framework in graphene films, and secondary pore structures are produced once removing the spheres. Based on hierarchically porous 3D GFs with large surface area, excellent binding strength, high conductivity, and distinct interfacial micro-environments, selected examples of electrochemical aptasensors are constructed for the assay of adenosine triphosphate (ATP) and thrombin (Tob) respectively. Sensitive ATP and Tob aptasensors, with high selectivity, excellent stability, and promising potential in real serum sample analysis, are established on 3D GFs with different structures. The results demonstrate that the surface area, as well as interfacial micro-environments, plays a critical role in the molecular recognition. The developed reliable and scalable protocol is envisaged to become a general path for in situ fabrication of more graphene films and the as-synthesized 3D GFs would open up a wide horizon for potential applications in electronic and energy-related systems.